ATSAR ISTIKHDÂM AL-DRAMÂ WAFQ MANAHI MASRAHAH AL-MANÂHIJ FÎ TANMIYAH AL-FAHM AL-QIRÂÎ FÎ AL-LUGHAH AL-'ARABIYAH LADA THÂLIBÂT AL-SHAF AL-SÂBI' AL-ASÂSÎ FÎ MAAN - Saleh Mohammad Abu-Taweeleh; Mustafa Odeh Jwaifell (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
This study aimed at measuring the impact of using curricula dramatization on Arabic language Understanding among seventh graders students in Ma'an. The study sample consisted of (43) female students distributed randomly onto two groups: (20) control group and (23) experimental group. The control group taught traditionally while the experimental groups taught by dramatization the curriculum. Achievement exam where used to measure Arabic language reading understanding. Result of ANCOVA showed significant statistics at a≤0.05 for the benefit of experimental group. The study recommended encouraging teachers to use drama approach in teaching and learning Arabic language.